Inheritance Law Politics: The Implementation in Muslim-Nonmuslim Families in Southern Thailand - Lathifah, Anthin; Briliyan Erna Wati; Mustakama Waeduereh; Nipatimoh Phudaro (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
The applicable law in a country is determined by the politics, including Muslim-non-Muslim inheritance law applicable in the Southern Thailand region, which is a Muslim-majority region in a Buddhist-majority country. The article aimed to describe the influence of politics in determining the implementation of Muslim-non-Muslim inheritance law in Thailand. The article was the result of socio-legal research with a legal political approach. Primary data sources were obtained from interviews with civil courts, Ulama at the Islamic Religious Council, parties involved in legal assistance in court, and Muslim-non-Muslim families who carry out inheritance law division. Meanwhile, secondary data were obtained from relevant documents. The study showed that the politics in Thailand have implications for the flexibility of inheritance law in Muslim-Non-Muslim families, which consists of three inheritance distribution patterns. First, Optional of the family is free to determine the law used in the inheritance division. This pattern is practiced by the majority pattern implemented in Thailand. Second, compromise, namely the Court and the Islamic Religious Council compromise to determine Muslim-non-Muslim inheritance law. And, Contestation, Islamic law contests with Buddhist law. The pattern of inheritance distribution between Muslim and non-Muslim families in Thailand shows flexibility of the state in implementing civil inheritance law. Also, the position of Islamic family law, especially inheritance law, is considered quite strong.